2007
DOI: 10.1523/jneurosci.0587-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Pathological Tau Species and Memory Loss in a Conditional Model of Tauopathy

Abstract: Neurofibrillary tangles (NFTs) are a pathological hallmark of Alzheimer's disease and other tauopathies, but recent studies in a conditional mouse model of tauopathy (rTg4510) have suggested that NFT formation can be dissociated from memory loss and neurodegeneration. This suggests that NFTs are not the major neurotoxic tau species, at least during the early stages of pathogenesis. To identify other neurotoxic tau protein species, we performed biochemical analyses on brain tissues from the rTg4510 mouse model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
403
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(429 citation statements)
references
References 43 publications
(73 reference statements)
25
403
1
Order By: Relevance
“…Thus, NFTs are not required for and may not be the primary cause of neurotoxicity and cognitive dysfunction. In fact, levels of early Tau multimeric aggregates that preceded NFTs correlated with memory deficits in transgenic mice that overexpress Tau (25). Collectively, these studies strongly suggest that an intermediate Tau aggregate preceding NFT formation may be responsible for neuronal dysfunction observed in AD and other tauopathies.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 74%
“…Thus, NFTs are not required for and may not be the primary cause of neurotoxicity and cognitive dysfunction. In fact, levels of early Tau multimeric aggregates that preceded NFTs correlated with memory deficits in transgenic mice that overexpress Tau (25). Collectively, these studies strongly suggest that an intermediate Tau aggregate preceding NFT formation may be responsible for neuronal dysfunction observed in AD and other tauopathies.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 74%
“…These types of studies will benefit greatly from new in vivo staining compounds that differentially bind soluble, prefibrillar, and aggregated tau. Even within these limitations, however, our present findings call into question therapeutic strategies aimed at preventing or disrupting fibrillar tau deposits (30), which may indeed sequester more toxic soluble tau species (31,32).…”
Section: Significancementioning
confidence: 79%
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014). In addition, we have also demonstrated that Aβ oligomers modulate the development of tau pathology and accelerate cognitive and synaptic impairments (Chabrier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%